Pengaruh Teknologi Digital dan Manajemen Waktu terhadap Kinerja Melalui Mediasi Work Life Balance - Rina Cristiningsih; Osly Usman (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2026)
This study aims to analyze the influence of information technology on performance, the influence of time management on performance, the influence of information technology moderated by work-life balance on performance, and the influence of time management moderated by work-life balance on performance. The research uses a quantitative method. The primary data source is obtained through questionnaires, with purposive sampling as the data collection technique. Data analysis is conducted using partial least squares (PLS) with the SmartPLS 4.0 application. The results show that digital technology has a negative and insignificant effect on the performance of working students. In contrast, time management has a positive and significant effect on the performance of working students. Furthermore, digital technology has a positive but insignificant effect on the work-life balance of working students. Time management, on the other hand, has a positive and significant effect on the work-life balance of working students. Work-life balance itself has a significant effect on the performance of working students. The findings indicate that digital technology has a positive but insignificant effect on performance through work-life balance, while time management has a significant effect on performance through work-life balance letters.